Exploration of cerebral hemodynamic pathways through which large artery function affects neurovascular coupling in young women - Cilhoroz, Burak T.; DeBlois, Jacob P.; Lefferts, Wesley K.; Keller, Allison P.; Pagan Lassalle, Patricia; Meyer, Michelle L.; Stoner, Lee; Heffernan, Kevin S. (Frontiers in Cardiovascular Medicine, 2022)
Background The interactions between large artery function and neurovascular coupling (NVC) are emerging as important contributors to cognitive health. Women are disproportionally affected by Alzheimer's disease and related dementia later in life. Understanding large artery correlates of NVC in young women may help with preservation of cognitive health with advancing age. Purpose To explore the association between large artery function, NVC and cognitive performance in young women. Methods Vascular measurements were made in 61 women (21 ± 4 yrs) at rest and during a cognitive challenge (Stroop task). Transcranial Doppler was used to measure left middle cerebral artery (MCA) maximum velocity (Vmax), mean velocity (Vmean), and pulsatility index (PI). NVC was determined as MCA blood velocity reactivity to the Stroop task. Large artery function was determined using carotid-femoral pulse wave velocity (cfPWV) as a proxy measure of aortic stiffness and carotid ultrasound-derived measures of compliance and reactivity (diameter change to the Stroop task). Cognitive function was assessed separately using a computerized neurocognitive battery that included appraisal of response speed, executive function, information processing efficiency, memory, attention/concentration, and impulsivity. Results MCA Vmax reactivity was positively associated with executive function (β = 0.26, 95% CI 0.01–0.10); MCA Vmean reactivity was negatively associated with response speed (β = −0.33, 95% CI −0.19 to −0.02) and positively with memory score (β = 0.28, 95% CI 0.01–0.19). MCA PI reactivity was negatively associated with attention performance (β = −0.29, 95% CI −14.9 to −1.0). Path analyses identified significant paths (p < 0.05) between carotid compliance and carotid diameter reactivity to select domains of cognitive function through MCA reactivity. Conclusions NVC was associated with cognitive function in young women. Carotid artery function assessed as carotid compliance and carotid reactivity may contribute to optimal NVC in young women through increased blood flow delivery and reduced blood flow pulsatility.